Analisis Penyebab Terjadinya Pekerjaan Repair pada PT. Lubuk Minturun Konstruksi Persada (PT. LMKP) Padang - Sari, Kharisma Permata; Arman, Utami Dewi; Desfita, Mediana; Nasmirayanti, Rita (JURNAL RIVET, 2025)
This study aims to determine the factors that cause repair work. To find out the factors that cause the most dominant repair work and to find out how to minimize repair work at PT Lubuk Minturun Konstruksi Persada (PT.LMKP) Padang. The method used is SPSS (Statistical Product and Service Solutions). By circulating a questionnaire of 50 respondents. The results of data analysis concluded that the indicators causing repair work consisted of design and documentation totaling 6 indicators, planning and scheduling totaling 6 indicators, materials and equipment totaling 6 indicators, human resources totaling 6 indicators, leadership and documentation totaling 6 indicators. So the total is 28 indicators of the causes of repair work. The indicator that causes the most dominant repair work is the indicator that has the highest score, namely Design and Scheduling for indicator X2.5 “repair work causes inequality between architectural drawings and structural drawings / not according to drawings” with a total score of 229 and an average of 4.58, the most dominant factor causing repair work at PT Lubuk Minturun Konstruksi Persada (PT LMKP) Padang, Design and Scheduling and finding ways to minimize the occurrence of repair work.